2012
DOI: 10.1016/j.dcn.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Early adversity and neural correlates of executive function: Implications for academic adjustment

Abstract: Early adversity can negatively impact the development of cognitive functions, although little is known about whether such effects can be remediated later in life. The current study examined one facet of executive functioning — inhibitory control — among children who experienced institutional care and explored the impact of a foster care intervention within the context of the Bucharest Early Intervention Project (BEIP). Specifically, a go/nogo task was administered when children were eight years old and behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
120
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 77 publications
9
120
1
1
Order By: Relevance
“…During the last three decades, the importance of EF integrity for human adaptation to the environment lead to an increase of researches aimed to understand the origin and development of such processes (Bernier, Carlson, Deschenes, & Matte-Gagné, 2012;Conway & Stifter, 2012;Diamond, 2001Diamond, , 2002Diamond, , 2013McDermott, Westerlund, Zeanah, Nelson, & Fox, 2012;Posner, Rothbart, Sheese, & Voelker, 2012;Welsh, Pennington, & Groisser, 1991). The implementation and expansion of such studies required the establishment of adequate EF tests for its application with children.…”
Section: Introductionmentioning
confidence: 99%
“…During the last three decades, the importance of EF integrity for human adaptation to the environment lead to an increase of researches aimed to understand the origin and development of such processes (Bernier, Carlson, Deschenes, & Matte-Gagné, 2012;Conway & Stifter, 2012;Diamond, 2001Diamond, , 2002Diamond, , 2013McDermott, Westerlund, Zeanah, Nelson, & Fox, 2012;Posner, Rothbart, Sheese, & Voelker, 2012;Welsh, Pennington, & Groisser, 1991). The implementation and expansion of such studies required the establishment of adequate EF tests for its application with children.…”
Section: Introductionmentioning
confidence: 99%
“…Research on institutionalized children, which reveals both neural markers of lack of attention/response monitoring, and behavioral inaccuracy in performing a required response, highlights this as a major difficulty in these children (Loman et al, 2013;McDermott, Westerlund, Zeanah, Nelson, & Fox, 2012). Consistent with the two studies just cited, the behavioral performance of institutionalized children in the current study (i.e., error of omission of a response in Go trials, but accuracy in inhibiting a response in No-go trials) reflects difficulties in sustained attention, rather than selective attention or inhibitory control.…”
mentioning
confidence: 99%
“…According to the pattern of impulsivity described on this group in previous works [18], we expected a lower amount of money accumulated in the institutionalized group as a result of a series of emotional reactions related with unfair proposals (75% of the total trials). INST adolescents would be less able to sacrifice some financial gain in order to get some money perhaps according to a higher socioemotional reactivity.…”
Section: Ultimatum Game Performancementioning
confidence: 77%
“…In relation with behavioral and cognitive consequences, diverse studies have found that the institutionalized children present impulsivity [18], social problems and delinquent behavior [19], as well as, affectation in cognitive functions like working memory, inhibitory control, memory for faces and visual attention [2,5]. Talking about social abilities, it has been demonstrated that children that was previously institutionalized and were randomly assigned to a foster care intervention program have better social abilities with less social communication problems compared to institutionalized children [20].…”
Section: Institutionalization and Brain/cognitive Affectationmentioning
confidence: 99%
See 1 more Smart Citation